Combating loneliness: The role of neighbourhood ICT, environmental attractiveness, and a sense of belonging to a local community - Latikka Rita; Savela Nina; Rubio-Hernandez Rosana; Koivula Aki; Makkonen Jouko; Nieto Fernandez Fernando; Vaananen Kaisa; Oksanen Atte (WILEY, 2025)
Neighbourhoods can provide a sense of belonging to a local community and support subjective well-being. Our goal was to gain novel insight into the value of neighbourhood information and communication technology (ICT) in combating loneliness. Furthermore, we were interested in how a sense of belonging to a local community can be a potential mediating factor and the role of environmental attractiveness. We used data from a nationwide survey of Finnish respondents (N = 1,226) and structural equation modelling for data analysis. We found that perceived environmental attractiveness and a sense of belonging to a local community were negatively associated with loneliness, while the use of neighbourhood ICT was positively associated with loneliness. Perceived environmental attractiveness and use of neighbourhood ICT were positively associated with a sense of belonging to a local community. Perceived environmental attractiveness and use of neighbourhood ICT were negatively associated with loneliness via a sense of belonging to a local community. Our results suggest that perceived environmental attractiveness and use of neighbourhood ICT could help reduce loneliness by enhancing a sense of belonging to a local community. Interventions aimed at improving perceived environmental attractiveness and individuals' senses of belonging to a local community could be particularly helpful in combating loneliness. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement.